Feminist Policy Analysis on Gender Mainstreaming Policy in Indonesian International Peacekeeping Forces - Zahra Ayu Kusuma Ricarvy; Sri Lestari Wahyuningroem (Jurnal Politik)
This study analyzes the implementation of gender mainstreaming policies within the Garuda troops using the Feminist Policy Analysis (FPA) approach in the context of Indonesia's commitment to gender equality in peacekeeping operations. Gender mainstreaming policies are expected to ensure equal access, participation, control, and benefits for both women and men within the defense system, as well as minimize gender discrimination. The method used in this research involves policy analysis as regulated in Presidential Instruction No. 9/2000, with a focus on its application in Peacekeeping Missions (IPM). Data were collected through interviews with relevant officials from the Ministry of Defense and the Ministry of Foreign Affairs, as well as through a review of relevant policy documents. The results of the study indicate that although some steps have been taken and policies have been implemented, these efforts are still insufficient in promoting gender mainstreaming by involving more women in IPM. The FPA analysis reveals that existing policies are ineffective in increasing women's participation and tend to place them in supportive roles. These policies still exhibit unconscious gender biases and do not provide specific incentives to enhance women's involvement in more significant roles. The conclusion of this research is that the implementation of gender mainstreaming policies in Indonesia still requires significant improvements.